A chemo-mechanical fracture model for the welding interface of vitrimers. (September 2020) - Meng, Qinghua
Highlights: Chemo-mechanical fracture model accounting for the vitrimer welding interface. Network structure evolution by combining polymer diffusion with chemical reaction. Fracture toughness obtaining by integrating dissipated energy in the cohesive region. Exponential shape function representing stretching profile of polymer chain network. Abstract: The welding of thermosetting polymers is a longstanding challenge in polymer science and engineering. Recently, developed dynamic covalent polymers (also known as vitrimers) provide a promising strategy for achieving interface welding. An understanding of the fundamental physical mechanisms underlying interfacial welding and fracture behavior is critically required to thoroughly explore the full potential of this technique. To this end, in this paper, we develop a chemo-mechanical fracture model to account for the toughness of the welding interface in vitrimers. The evolution of the interfacial vitrimer network microstructure in the welding is modeled by using a bamboo joint-like structural model. Based on the evolution of the network structure, the fracture toughness of the welding interface is formulated by integrating the dissipated strain energy in the cohesive region ahead of the interfacial crack, in which a shape function with an exponential form is proposed to describe the strain profile of the vitrimer networks. Our theoretical model also correlates interfacial fracture toughness with welding temperature and time. An optimal range of welding temperature to time is identified to achieve a higher toughness of the welding interface. We show that a larger cohesive region induced by enhancing the vitrimer network structure results in an elevated interfacial fracture energy. The results predicted by our model are in good agreement with the relevant experimental measurements. This work might help to decipher the toughening mechanisms for the welding interface of vitrimers.